Pogostnost endometrioze pri zdravih in neplodnih ženskah - Mohar, Janez (Medicinski razgledi, 2004)
Background: Endometriosis involves an appearance of endometriotic tissue with all of its histological and functional properties outside the uterine cavity. The frequency of endometriosis in women of reproductive age without symptoms and signs of disease remains unknown. This disease is probably the most frequent cause of infertility and impaired fertility. Objective: The objective of our study was to estimate the frequency of endometriosis in a population of healthy women and to define endometriosis as an important cause of infertility. Patients and methods: The study was carried out retrospectively. The women were divided into 2 groups. In the first group, there were 378 healthy asymptomatic women who wanted laparoscopic sterilization. In the other one, there were 111 primarily and secondarily infertile women, on whom diagnostic laparoscopy was performed in order to discover the cause of their infertility. From medical records of all the patients, medical history and laparoscopic data were gathered about the frequency and status of endometriosis, clinical symptoms and age. These data were compared between healthy and infertile women and between primarily and secondarily infertile women. The statistically significant difference was evaluated at p is less or equal 0.05. Results: The frequency of endometriosis in the group of infertile women (33 %) was significantly higher (p=0.001) than in the group of healthy women (3.7 %). In most cases, minimal endometriosis was found in both groups (57 % vs. 86 %). The difference in the frequency of endometriosis between the groups of primarily and secondarily infertile women was not statistically significant. Endometriosis represented the most frequently found pathology (33 %) in the group of infertile women. Conclusions: Endometriosis is present in a relatively high number women and is also the most commonly found pathology among infertile women.
Keywords: Infertility, female; Neplodnost, ženska; Endometriosis; Endometrioza; Laparoscopy; Laparoskopija; ginekologija; diagnostika; neplodnost; therapy; zdravljenje